2021
DOI: 10.3389/fimmu.2021.669347
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Lymphocytes Target HIV-1 Gag Through Granzyme M-Mediated Cleavage

Abstract: Untreated HIV-1 infection leads to a slow decrease in CD4+ T cell lymphocytes over time resulting in increased susceptibility to opportunistic infections (acquired immunodeficiency syndrome, AIDS) and ultimately death of the infected individual. Initially, the host’s immune response controls the infection, but cannot eliminate the HIV-1 from the host. Cytotoxic lymphocytes are the key effector cells in this response and can mediate crucial antiviral responses through the release of a set of proteases called gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Among the HIV- 1 viral proteins, the reverse transcriptase (RT), because of its essential role in replication and because it is the main target of ART, has been extensively studied [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. In addition, the proteins of the gag gene are involved in the virion structure and also in the cellular immune response [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Apart from these proteins, the viral envelope gene ( env ) and the derived glycoprotein complex (Env) have attracted numerous studies because of their central role in (i) the initial events (CD4 and co-receptor binding, pore fusion formation) and subsequent step of the biological viral life cycle; (ii) the neutralizing humoral immune response; and (iii) the viral tropism.…”
Section: Introductionmentioning
confidence: 99%
“…Among the HIV- 1 viral proteins, the reverse transcriptase (RT), because of its essential role in replication and because it is the main target of ART, has been extensively studied [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. In addition, the proteins of the gag gene are involved in the virion structure and also in the cellular immune response [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Apart from these proteins, the viral envelope gene ( env ) and the derived glycoprotein complex (Env) have attracted numerous studies because of their central role in (i) the initial events (CD4 and co-receptor binding, pore fusion formation) and subsequent step of the biological viral life cycle; (ii) the neutralizing humoral immune response; and (iii) the viral tropism.…”
Section: Introductionmentioning
confidence: 99%
“…These cells can eliminate virus-infected cells through the induction of target cell death via multiple mechanisms ( 13 15 ). In a previous study, we showed that NK cells target the HIV-1 Gag protein through the release of protease granzyme M (GrM) ( 16 ). Because GrM is known to inhibit replication of other viruses ( 17 19 ), we were initially interested in whether NK cells could also inhibit HIV-1 replication in a GrM-dependent manner.…”
Section: Introductionmentioning
confidence: 99%